Preservation of Peri-Implant Papilla: A Narrative Review - Venkatesh, Nandita; Shetty, Manoj; John, Nivya (Journal of Health and Allied Sciences NU, 2022)
Beside osseointegration and restoration of function, the patient's subjective satisfaction with the esthetic result is a touchstone of the success of implant therapy. The long-term maintenance and reconstruction of papilla-like soft tissue between two adjacent implants in the esthetic zone which is esthetically satisfactory is generally regarded as a challenge. The road to success is much more complicated with implants, because of biologic and anatomical limitations of peri-implant tissues. Numerous techniques have been proposed to manage the hard and soft tissues in an attempt to achieve ideal esthetic results which includes surgical and nonsurgical techniques. The goal of reconstructive procedures is to provide peri-implant bone that supports and maintains gingival contours. An interdisciplinary approach has an obvious advantage of long-term preservation of a healthy peri-implant tissue which is of key importance in ensuring acceptable function and subjective satisfaction of esthetics of dental implants. A detailed literature search was performed in English language from 1986 to 2012, which included review articles, original research, as well as case reports. The search was performed in National Library of Medicine's PubMed database, Google Search, and Science Direct. A manual search of hard copies of available journal was also performed using interdental papilla, peri-implant papilla, esthetics, and dental implant as key words, in an attempt to gain insight into the limitations of papilla preservation, the factors which may potentially affect the maintenance and reconstruction of inter-implant papilla, and the contemporary methods to augment it.
Keywords: dental implants; peri-implant papilla; interdental papilla